Pengaruh Kompleksitas Operasi Perusahaan, Financial Distress, dan Kepemilikan Institusional Terhadap Audit Report Lag Dengan Ukuran Perusahaan Sebagai Pemoderasi - Tomi Riyadi; Naila Syaida Ullaya (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The aim of this research is to determine the influence of Company Operational Complexity, Financial Distress, and Intitutional Ownership on Audit Report Lag with Company Size as a moderating variable. The method used in this research is associative quantitative, using secondary data. The population of this research is LQ45 indeks companies listed on the Indonesia Stock Exchange for the 2019-2023 period, namely 45 companies. With the research sample method using purposive sampling with specific criteria, the total sample used was 20 companies so that observations amounted to 100 data. Data analysis in this research uses descriptive statistical analysis, panel data regression model estimation, classical assumption testing. Hypothesis testing and Moderated Regression Analysis (MRA) using eviews 12. The result of this research are that complexity of company operations has no effect on the audit report lag.the Financial Distress has no effect on the Audit Report Lag. Intitutional Ownership has an effect on Audit Report Lag. And for the moderating variable, Company Size can only strengthen the relationship between Intitutional Ownership and Audit Report Lag, while Company Size weakens the relationship between Company Operational Complexity and Audit Report Lag, and Company Size weakens the relationship between Financial Distress and Audit Report Lag.